Charitable giving and income: Households with high income donate less than poorer households relative to their disposable income - Karsten Schulz-Sandhof; Jürgen Schupp (DIW Weekly Report, 2022)
For the first time in 2020, the Socio-Economic Panel (SOEP), an annual survey of private households, surveyed the donation behavior of a random sample of high net worth individuals that had been added in 2019. As a result of this sample, the volume of private donations increased from 9.7 to 10.3 billion euros in 2019, despite the fact that fewer individuals donated and the donation rate was lower (46.8 percent vs. 43.3 percent) than in 2017. The donation volume for 2021 will increase to 12.9 billion euros, its development extrapolated using the DZI Donation Index (DZI Spenden-Index). Socio-economic analyses of SOEP data show that income has a clear influence on donation behavior. Although the richest ten percent of households contribute 37 percent of total donations, they donate less than the poorer income groups relative to their disposable income. Despite this, the tax benefit from charitable giving is greater for richer households than for poorer because it is based on the marginal tax rate. Equal tax treatment for donors regardless of income could increase the willingness to donate.
Keywords: D31; D64; Z13; 330; donations; charitable giving; income; SOEP